Interaction between nighttime MSTID and mid-latitude field-aligned plasma depletion structure over the transition region of geomagnetic low-mid latitude: First results from Hanle, India. (June 2021) - Yadav, V.; Rathi, R.; Gaur, G.; Sarkhel, S.; Chakrabarty, D.; Sunil Krishna, M.V.; Pavan Chaitanya, P.; Patra, A.K.; Choudhary, R.K.; Pant, T.K.; Upadhayaya, A.K.
Abstract: In this paper, we study the interaction between a nighttime Medium Scale Traveling Ionospheric Disturbance (MSTID) and geomagnetic north-south oriented field-aligned plasma depletion structure over Hanle, Leh Ladakh (32.7°N, 78.9°E; Mlat. 24.1°N), India on a geomagnetically quiet night (06 May 2019, Ap = 4). The results are based on the observations carried out using a newly established airglow imager operating at 630.0 nm at Hanle which is a transition region of geomagnetic low-mid latitudes. A sequence of processes constituted this unique interaction that includes developing phase of the MSTID within the imager's field of view, gradual bending of the field-aligned plasma depletion structure and eventual merging with the MSTID, and propagation of the merged structure in the form of a single MSTID structure post-interaction. The mechanism appears to be controlled by unequal but oppositely directed polarization electric fields within the dark and bright bands of the developing MSTID, whose projection on the horizontal plane is observable in the airglow images. The present work is the first observation illustrating the interaction between a developing phase of MSTID and plasma depletion structure over a geomagnetic low-mid latitude transition region, which assumes importance for understanding the underlying plasma irregularity processes. Highlights: Unique interaction between a MSTID and a field-aligned plasma depletion over geomagnetic low-mid latitude transition region. The plasma depletion gradually tilted and got decayed on interacting with the MSTID resulting in a single MSTID structure. It is proposed that the unequal polarization electric fields within the developing MSTID facilitated the interaction.